Pengaruh Pelatihan dan Pengembangan SDM Terhadap Kinerja Pegawai di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi Lampung - Aulia, Khansa Najla; A.A, Iskandar (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the effect of training and human resource development on employee performance at the Capital Investment and One-Stop Integrated Service Office (DPMPTSP) of Lampung Province. This study uses a quantitative approach with a causal associative method. The population in this study were all ASN employees at DPMPTSP Lampung Province, totaling 95 people, with a sample of 30 respondents determined using the Yamane formula with a 15% error rate. The data collection technique was carried out by distributing questionnaires using a Likert scale. The data obtained were analyzed using multiple linear regression analysis with the help of the SPSS program, accompanied by validity tests, reliability tests, classical assumption tests, t-tests, F-tests, and coefficients of determination (R²). The results of the study indicate that partially training has a positive and significant effect on employee performance, and human resource development also has a positive and significant effect on employee performance. Simultaneously, training and human resource development have a significant effect on employee performance at DPMPTSP Lampung Province. The coefficient of determination (R²) value indicates that training and human resource development are able to explain most of the variation in employee performance, while the rest is influenced by other factors outside this study. Thus, improving the quality of training and human resource development in a structured and sustainable manner is expected to improve employee performance and the quality of public services.